VARIETIES AND MEDICINAL PROPERTIES OF CARROT (DAUCUS CAROTA L) GROWING IN UZBEKISTAN AND ABROAD - N.B.Atakulova,; G.A.Madaminova, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This in the article In Uzbekistan and edge in the country cultivated carrot species , varieties , botanical classification , distribution , chemical composition and amounts about information given . Carrot cultivation according to 5- year plans of countries indicators analysis was done . Carrot and his/her from the leaf people in medicine use methods scientific sources according to analysis was done .